Identification of Flucloxacillin-Haptenated HLA-B*57:01 Ligands: Evidence of Antigen Processing and Presentation. (29th July 2020) - Waddington, James C; Meng, Xiaoli; Illing, Patricia T; Tailor, Arun; Adair, Kareena; Whitaker, Paul; Hamlett, Jane; Jenkins, Rosalind E; Farrell, John; Berry, Neil; Purcell, Anthony W; Naisbitt, Dean J; et al.
Abstract: Flucloxacillin is a β-lactam antibiotic associated with a high incidence of drug-induced liver reactions. Although expression of human leukocyte antigen (HLA)-B*57:01 increases susceptibility, little is known of the pathological mechanisms involved in the induction of the clinical phenotype. Irreversible protein modification is suspected to drive the reaction through the modification of peptides that are presented by the risk allele. In this study, the binding of flucloxacillin to immune cells was characterized and the nature of the peptides presented by HLA-B*57:01 was analyzed using mass spectrometric-based immunopeptidomics methods. Flucloxacillin modification of multiple proteins was observed, providing a potential source of neoantigens for HLA presentation. Of the peptides eluted from flucloxacillin-treated C1R-B*57:01 cells, 6 putative peptides were annotated as flucloxacillin-modified HLA-B*57:01 peptide ligands (data are available via ProteomeXchange with identifier PXD020137). To conclude, we have characterized naturally processed drug-haptenated HLA ligands presented on the surface of antigen presenting cells that may drive drug-specific CD8+ T-cell responses.